PENGARUH PEMBERIAN BEBERAPA KONSENTRASI AIR KELAPA TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA (Coffea canephora) - Eviza, Andi; Azizi, Rahmat; Syariyah, Amaliyah; Amir, Syafri (Fakultas Pertanian Universitas Mataram, 2025)
The purpose of this study was to examine the effect of various concentrations of coconut water on the growth of Robusta coffee seedlings and to determine which concentration provided the best effect. This research was conducted at the Payakumbuh State Agricultural Polytechnic, Harau District, Lima Puluh Kota Regency, West Sumatra Province. The research was titled